ブンベツ ヨウカイ ホウ ニ ヨル ドンファン イケ ノ コア タイセキブツ チュウ ノ コウブツ シュ ヘノ カガク ゲンソ ノ ブンパイ ニ ツイテ - 冨山, 千里; トミヤマ, チサト; 北野, 康; キタノ, ヤスシ; Tomiyama, Chisato; Kitano, Yasushi (1982)
P(論文) 塩化カルシウム型の塩湖であるドンファン池から採取したコア堆積物を分別溶解法を用いて分析した。堆積物は, 1M酢酸可溶, 1M塩酸ヒドロキシルアミン+25%酢酸可溶, 1.2M塩酸可溶, フッ酸+過塩素酸可溶, の4フラクションに段階的に分別し, それらのフラクション中へのCa, Mg, Fe, Mn, Cu, Znの分配について, その深度分布を示した。また, 堆積物中に含まれるgypsumやcalciteへの微量金属の分配についても考察した。この方法は, ドンファン池の堆積物, および塩化カルシウム型の水の起源を議論するうえで, 有効であると考えられる。 A selective chemical leaching technique has been applied to the sediment core samples from Don Juan Pond in Antarctica, which is known as a very high calcium chloride saline pond. The vertical profiles are shown on the partitioning of Ca, Mg, Fe, Mn, Cu and Zn into the following four fractions of the sediment; 1M CH_3COOH soluble, 1M NH_2OH・HCl+25% CH_3COOH soluble, 1.2M HCl soluble and HClO_4+HF soluble fractions. The partitioning of trace metals into gypsum and calcite found in the sediment has been estimated. This may be helpful for the discussion on the formation processes of the sediment and also of the calcium chloride water in Don Juan Pond. departmental bulletin paper